Observations on the worm egg counts and their nematode species in goats from the north-east district of Penang Island, Peninsular Malaysia - A. Rahman, Wahab; Che' Ros, Adanan (Universiti Putra Malaysia, 1992)
The faecal worm egg counts and the prevalence of nematode species in goats from seven smallholder goat farms in the north-east district of Penang Island were investigated. Generally the egg counts were moderately heavy, ranging from 500 - 2000 epg. The climatic conditions of the distlict seemed favour able for the survival and development of at least five species of nematodes, namely Cooperia spp. Haemonchus spp., Oesophagostomun sfrp., Strongyloides spp., and Trichostrongylus spp., of which Haemonchus spp. seemed to predominate.